2017
DOI: 10.1016/j.peptides.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Bean peptides have higher in silico binding affinities than ezetimibe for the N-terminal domain of cholesterol receptor Niemann-Pick C1 Like-1

Abstract: Niemann-Pick C1 like-1 (NPC1L1) mediates cholesterol absorption at the apical membrane of enterocytes through a yet unknown mechanism. Bean, pea, and lentil proteins are naturally hydrolyzed during digestion to produce peptides. The potential for pulse peptides to have high binding affinities for NPC1L1 has not been determined. In this study , in silico binding affinities and interactions were determined between the N-terminal domain of NPC1L1 and 14 pulse peptides (5≥ amino acids) derived through pepsin-pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Peptides in rice bran protein hydrolysates were also found to inhibit cholesterol micellar solubilization and may be important in reducing cholesterol [19]. In a recent study, Hernandez et al [110] observed that black bean and cowpea derived peptide YAAAT could tightly bind to the N -terminal domain of Niemann-Pick C1 (NPC1L1) to disrupt interactions between NPC1L1 and membrane proteins to enhance cholesterol absorption. Duranti et al [111] also observed that consumption of the α′ subunit reduced plasma cholesterol levels by 36% and also upregulated liver β-very low density lipoprotein cholesterol receptors in rats.…”
Section: Food-derived Bioactive Peptides and Human Healthmentioning
confidence: 99%
“…Peptides in rice bran protein hydrolysates were also found to inhibit cholesterol micellar solubilization and may be important in reducing cholesterol [19]. In a recent study, Hernandez et al [110] observed that black bean and cowpea derived peptide YAAAT could tightly bind to the N -terminal domain of Niemann-Pick C1 (NPC1L1) to disrupt interactions between NPC1L1 and membrane proteins to enhance cholesterol absorption. Duranti et al [111] also observed that consumption of the α′ subunit reduced plasma cholesterol levels by 36% and also upregulated liver β-very low density lipoprotein cholesterol receptors in rats.…”
Section: Food-derived Bioactive Peptides and Human Healthmentioning
confidence: 99%
“…Therefore, there is an increasing demand in sourcing natural and food-based alternatives of these drugs. Hypocholesterolemic activity has been observed in some plant-based biopeptides, including ones from rice bran (Zhang et al, 2012), cowpea (Marques et al, 2015;Hernandez and de Mejia, 2017), cumin seed (Siow et al, 2016), and soy (Duranti et al, 2004;Lammi et al, 2015). Recently, Coelho et al (2018) hydrolysed chia seed protein into biopeptides using Alcalase and Flavourzyme.…”
Section: Hypocholesterolemic Activitymentioning
confidence: 99%
“…NPC1L1 is involved in the cholesterol absorption at the apical membrane of enterocytes through an unknown mechanism. The cowpea KD dipeptide and three black bean pea peptides (YAAAT, ERAF, and FATGT) were found in silico to have binding affinities to the N-terminal domain of NPC1L1 and were opined to have great potential to disrupt the interaction between NPC1L1 and membrane proteins facilitating cholesterol absorption better than Ezetimibe [325].…”
Section: Cowpea (Vigna Unguiculata (L) Walp)mentioning
confidence: 99%